Request Handling in Elastic Optical Data Center Networks: A Routing Algorithm Approach - Rodrigues, Edson Adriel Freitas (2025)
In recent years, worldwide communication has seen significant advancements driven by the growing demands of modern applications. These developments have introduced new requirements for data transfer, emphasizing the need for both high speeds and high efficiency. The cloud services model illustrates this shift, underscoring the importance of developing new mechanisms to handle increased data traffic. Beyond technological techniques, progress in the physical layer of networks is also crucial. It includes adopting spectrally and spatially flexible links that can precisely tune to the varying demands of network requests. In response to these challenges, this article proposes a routing algorithm tailored for Space-Division Multiplexing Data Center Elastic Optical Networks. The main objective of this algorithm is to improve network performance by maximizing the number of requests served efficiently. By taking advantage of the flexibility of optical networks, the proposed solution aims to enhance journal center capabilities while meeting the stringent requirements of modern communication systems. The potential of the proposed algorithm is seen in the Bandwidth Blocking Ratio, where it has better results than the other algorithms compared by up to two orders of magnitude, thus supporting the demands of the network.